Contemporary Trends in Economic Cybersecurity - Yu. Yu. Shitova; Yu. A. Shitov (Мир новой экономики, 2019)
This paper is devoted to the analysis of modern trends in economic cybersecurity. We analysed the dynamics of cyber-attacks over the past five years and, particularly, pointed on the main trends of 2018 year. Our analysis showed great diversity and variety of cyber-criminal actions: global espionage, financial attacks, card fraud, information theft and phishing, network attacks and traffic interception, cryptographers and extortionists, crypto-jacking. Further, we attempted to predict cyber threats that await us soon. We expected the main problems come from smart cyber-attacks, based on the latest technologies of artificial intelligence (AI) and machine learning (ML), as well as exploiting the vulnerabilities of the Internet of Things. Therefore, we ought to apply integrated approaches using the same innovative technologies. The cyber-crime industry will increasingly consolidate — the efforts will be focused on automating and streaming criminal cyber activities, and new technologies will further reduce the cost of searching for vulnerabilities. It means development of hacking tools while accelerating the speed and scale of attacks. We must implement an integrated, echeloned approach with the same innovative technologies of AI and MO used by hackers, to fight effectively with future cyber threats. Small and medium businesses will have the opportunity to purchase a cyber-defence service. An improvement of the internal IT culture in the company remains the critical issue, which is still a weak link in the chain and the target of cyber-attacks. We discuss the measures of legislative state support in Europe and Russia against cybercrime in the final section of the paper, followed by conclusion.